A NEW f-IDPS APPROACH FOR THE INTRUSION DETECTION IN HIGH-SPEED NETWORKS (International Journal of Engineering and Computer Science, 2017)
As the networks become faster and faster, the emerging requirement is to improve the performance of the Intrusion Detection and Prevention Systems (IDPS) to keep up with the increased network throughput. In high speed networks, it is very difficult for the IDPS to process all the packets. Since the throughput of IDPS is not improved as fast as the throughput of the switches and routers, it is necessary to develop new detection techniques other than traditional techniques. In this paper we propose a rule-based IDPS technique to detect Layer 2-4 attacks by just examining the flow data without inspecting packet payload. Our